Phytochemical screening, quantitative analysis and antioxidant activity of Lifago dielsii Schweinj. & Muschl. (Asteraceae) - Aïssaoui Hanane; Menad Ahmed; Mezhoud Samia; Ameddah Souad; Mekkiou Ratiba; Benayache Samir; Benayache Fadila (International Journal of Phytomedicine, 2014)
This study is designed to assess the phytochemical screening of Lifago dielsii Schweinj. & Muschl., endemic species localized in the South of Algeria, and to evaluate their potential antioxidant properties using 1,1-diphenyl-2-picrylhydrazyl (DPPH°) radical scavenging and lipid peroxidation inhibition (LPO; Fe2+/ascorbic acid system) assays. The phytochemical screening of the aerial parts of L. dielsii revealed the presence of triterpenoids, saponins, alkaloids, coumarins, flavonoids and tannins. Three fractions [chloroform (CHCl3), ethyl acetate (EtOAc), n-butanol (n-BuOH)] obtained from aqueous-MeOH extraction and the insoluble methanol (MeOH) part in water, were subjected to a quantitative determination of polyphenols and flavonoids. The antioxidant properties of all extracts were evaluated. The EtOAc fraction had the highest amount of total phenolic contents (TPC) compared to MeOH and n-BuOH) fractions whereas CHCl3 fraction showed the lowest level. The n-BuOH fraction was richer in total flavonoids content (TFC) (88.81%) compared to EtOAc (37.76%) and MeOH extract (37.88%). The CHCl3 fraction exhibited the weakest content of TFC (18.82%). The antioxidant activity revealed that the EtOAc extract seems to have the most powerful effect on the DPPH° scavenging effect (IC50=47.80 ± 2.20 µg/ml) and on LPO inhibition (IC50=113.24±0.65µg/ml). These results showed that L. dielsii would be suggested as a promising alternative source of the natural anti-oxidative phenolic compounds.